2014
DOI: 10.1515/ijcre-2012-0039
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a New Chemical-Looping Combustion Process without Sulfur Evolution Based on Ca-Based Oxygen Carrier

Abstract: Calcium sulfate (CaSO 4 ) is a promising oxygen carrier for chemical-looping combustion system. The release of sulfurous gas in the circulating of Ca-based oxygen carrier is a crucial problem. In this paper, it is found that the released amount of sulfurous gas is greatly affected by the partial pressure of reductive gas. If the partial pressure of the mixed reductive gases, composed of H 2 and CO, maintains higher than 40 kPa, the sulfurous gas can be completely eliminated even at the reacting temperature hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It was found that CaS was the dominant compound after CaSO 4 reduction at 900 ºC, whereas the presence of CaO was more relevant at 950 ºC. Further works have also observed the same effect of the temperature on side reactions [27][28][29][30].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…It was found that CaS was the dominant compound after CaSO 4 reduction at 900 ºC, whereas the presence of CaO was more relevant at 950 ºC. Further works have also observed the same effect of the temperature on side reactions [27][28][29][30].…”
Section: Introductionmentioning
confidence: 75%
“…Several authors have evaluated the use of anhydrite ore, a mineral which is mainly composed of CaSO 4 , for CLC [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]; but not sulphated limestone. Song et al [26] observed that both reduction R1 and side reactions R4 and R7 were enhanced by increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of CaO on the concentration of sulfurous gas during the CLG of coal was evaluated through the following experiments. According to side reactions R6-R13 [19][20][21], sulfurous gasses, such as H 2 S, COS and SO 2 , may be formed during the CaSO 4 reduction process in the fuel reactor. During the experiment, the concentration of SO 2 was so low that these gasses could be neglected (i.e., their concentrations were below the detection limit of 0.001%).…”
Section: Sulfur Release With Caso 4 /Ben and Caso 4 -Cao/ben Oxygen Cmentioning
confidence: 99%
“…First, the gasification of coal is considered to be the rate-limiting step, and CaSO 4 oxygen carriers inefficiently catalyze coal gasification. Second, the release of sulfurous gas and the formation of calcium oxide (CaO) are unavoidable during the CaSO 4 reduction process in the fuel reactor due to side reactions R6-R13 [19][20][21]. If CaO is formed, the oxygen transport capacity and heat release of CaSO 4 oxygen carriers in the CLG progress are eliminated.…”
Section: Introductionmentioning
confidence: 99%